Antihypertensive treatment changes and related clinical outcomes in older hospitalized patients. (21st December 2022) - Cicco, Sebastiano; D′Abbondanza, Marco; Proietti, Marco; Zaccone, Vincenzo; Pes, Chiara; Caradio, Federica; Mattioli, Massimo; Piano, Salvatore; Marra, Alberto Maria; Nobili, Alessandro; Mannucci, Pier Mannuccio; Pietrangelo, Antonello; et al.
Abstract: Background: Hypertension management in older patients represents a challenge, particularly when hospitalized. Objective: The objective of this study is to investigate the determinants and related outcomes of antihypertensive drug prescription in a cohort of older hospitalized patients. Methods: A total of 5671 patients from REPOSI (a prospective multicentre observational register of older Italian in‐patients from internal medicine or geriatric wards) were considered; 4377 (77.2%) were hypertensive. Minimum treatment (MT) for hypertension was defined according to the 2018 ESC guidelines [an angiotensin‐converting‐enzyme‐inhibitor (ACE‐I) or an angiotensin‐receptor‐blocker (ARB) with a calcium‐channel‐blocker (CCB) and/or a thiazide diuretic; if >80 years old, an ACE‐I or ARB or CCB or thiazide diuretic]. Determinants of MT discontinuation at discharge were assessed. Study outcomes were any cause rehospitalization/all cause death, all‐cause death, cardiovascular (CV) hospitalization/death, CV death, non‐CV death, evaluated according to the presence of MT at discharge. Results: Hypertensive patients were older than normotensives, with a more impaired functional status, higher burden of comorbidity and polypharmacy. A total of 2233 patients were on MT at admission, 1766 were on MT at discharge. Discontinuation of MT was associated with the presence of comorbidities (lower odds for diabetes, higher odds for chronic kidney disease and dementia). An adjusted multivariable logistic regression analysis showed that MT for hypertension at discharge was associated with lower risk of all‐cause death, all‐cause death/hospitalization, CV death, CV death/hospitalization and non‐CV death. Conclusions: Guidelines‐suggested MT for hypertension at discharge is associated with a lower risk of adverse clinical outcomes. Nevertheless, changes in antihypertensive treatment still occur in a significant proportion of older hospitalized patients. Abstract : In this observational cohort study, we investigated the impact of hospitalization on changes in antihypertensive therapy in 5671 hypertensive older inpatients from the REPOSI register. Fifty‐one percent of patients were on minimum treatment (MT, defined according to the 2018 ESC guidelines) at admission. This percentage reduced to 40% at discharge, mostly due to specific clinical impairment and comorbidities such as chronic kidney disease and dementia. Maintaining a MT at discharge was associated with a lower risk of major clinical outcomes.